Using patient complaints to drive healthcare improvement: a narrative overview. Issue 1 (13th October 2021) - Pearce, Matthew; Wilkins, Victoria; Chaulk, David
ABSTRACT: Patient complaints are directly related to patient experience and safety. While complaints have the potential to be a major driving force in quality improvement, there is little evidence-based structure to use as a guide. The existing literature draws attention to the significant variability in complaint reporting and analysis systems as major barriers. Furthermore, weak change strategies are frequently implemented in response to complaints. This often prevents further investigation into larger systems issues that could be addressed with quality improvement initiatives. Several recent studies describe success with the use of a standardized tool to classify patient complaints, which highlights attempts at overcoming these barriers. There are opportunities to more effectively use patient complaints to drive improvement including a cultural shift with supportive leadership, transparency with the complaint process, and the use of a standardized tool to better organize and process complaints.